Study on molecular structure for Bupropion and its Derivatives using Quantum Mechanics Methods (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Quantum chemical calculation was correlated with geometrical structure and total energy of Bupropion and its five derivatives. Theoretical vibrational frequencies and geometric parameters (bond lengths) have been calculated using ab initio (HF), density functional theory (B3LYP), semi-empirical (AM1, PM3) methods with different basis sets to design the Bupropion drugs and its derivatives by a Gaussian 09 W program with GUI(Graphical User interface) called Gauss View 5.08. Theoretical optimized geometric parameters and vibrational frequencies of Bupropion have been compared with the corresponding five derivatives data. The highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energies have been determined. The theoretical study includes the calculation of the thermodynamic properties of the drugs and its derivatives like zero-point energy, enthalpy, entropy, ionization energy, electron affinity to make a correlation between the gained results. the drug was Bupropion as an antidepressant and drug adduct treatments. The theoretical different methods showed that the derivatives (4) are one of the best addicts which have a drug charactors.